A Death in the Family: Disability Activism, Mourning, and Diagnostic Kinship - Lewis, Elizabeth (Disability Studies Quarterly, 2016)
This article utilizes data from ethnographic research on deafblindness advocacy in Guatemala to show how families in this community create new forms of kinship with one another based on their children's shared diagnosis. The category of deafblindness expanded significantly in recent decades and now describes a diverse disability population. This case study shows that the umbrella diagnosis of deafblindness opens new possibilities for community formation and belonging, granting diagnostic intelligibility to children who would have received an ambiguous label of having "multiple disabilities" in the recent past. By proposing the concept of diagnostic kinship, this essay demonstrates that diagnoses can offer not only affective and logistical support, but can also generate new kinship possibilities and forms that are contingent on biomedical categories.